2011
DOI: 10.4103/0974-2700.82209
|View full text |Cite
|
Sign up to set email alerts
|

Blunt splenic injury in Sikkimese children and adolescents

Abstract: Background:The contemplation for the salvage operations and the nonoperative treatment for the pediatric splenic injuries had increasingly been suggested as the standard case management.Objectives:The study was carried out to identify the risk factors, the presentations, the severities and outcome of the interventions of blunt splenic injuries in the children and adolescents.Materials and Methods:This retrospective review was carried out in a tertiary care hospital in Sikkim on the children and adolescents adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Road traffic accidents have been reported to be the commonest cause of blunt splenic injuries in most studies as supported by the present study [ 7 , 11 , 13 , 15 , 17 ]. In contrast to our findings, one study reported fall from height as the most common cause of splenic injuries [ 21 ]. High incidence of road traffic accidents in our study may be attributed to recklessness and negligence of the driver, poor maintenance of vehicles, driving under the influence of alcohol or drugs and complete disregard of traffic laws.…”
Section: Discussioncontrasting
confidence: 99%
“…Road traffic accidents have been reported to be the commonest cause of blunt splenic injuries in most studies as supported by the present study [ 7 , 11 , 13 , 15 , 17 ]. In contrast to our findings, one study reported fall from height as the most common cause of splenic injuries [ 21 ]. High incidence of road traffic accidents in our study may be attributed to recklessness and negligence of the driver, poor maintenance of vehicles, driving under the influence of alcohol or drugs and complete disregard of traffic laws.…”
Section: Discussioncontrasting
confidence: 99%